2008
DOI: 10.1007/s00540-007-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

The degree of newly emerging mitral regurgitation during off-pump coronary artery bypass is predicted by preoperative left ventricular function

Abstract: Preoperative LV dysfunction is a predictor of severe mitral regurgitation during OPCAB. When poor LV function is suggested, it is necessary to be prepared for further hemodynamic deterioration caused by mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In an experimental study, Koga,et al 20) showed that cardiac displacement alone did not cause MR when coronary perfusion was maintained, and occlusion of the LAD rarely caused MR; however, occlusion of the left circumflex artery (LCx) caused MR from the posteromedial site. In a clinical study, Akazawa, et al 21) reported the relationship between left ventricular function and the severity of MR during OPCAB. MR was the most severe during anastomosis of the LCx, and 39% of the patients had moderate to severe MR during anastomosis of the LCx.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…In an experimental study, Koga,et al 20) showed that cardiac displacement alone did not cause MR when coronary perfusion was maintained, and occlusion of the LAD rarely caused MR; however, occlusion of the left circumflex artery (LCx) caused MR from the posteromedial site. In a clinical study, Akazawa, et al 21) reported the relationship between left ventricular function and the severity of MR during OPCAB. MR was the most severe during anastomosis of the LCx, and 39% of the patients had moderate to severe MR during anastomosis of the LCx.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…Multivariate logistic analysis of the incidence of MACE with a mean PAP of > 18.8 mmHg, a mean CVP of > 7.5 mmHg, and significant baseline characteristics in Table 2 as explanatory variables showed that PAP (odds ratio [OR], 3.77; 95% CI, 1.52 to 9.35) and an NYHA classification of 3 or 4 (OR, 3.50; 95% CI, 1.32 to 9.26) were significantly associated with the development of MACE (Table 4 ). The presence of mitral regurgitation (MR), anastomoses in the left circumflex artery (LCX), and end-stage renal disease remained potential contributors to pulmonary congestion [ 13 ]. However, these characteristics did not yield a P value of < 0.05 in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…2,7 The degree of emerging MR during mechanical heart displacement in OPCAB has been demonstrated to be associated with poor LVEF. 23 Moreover, considering that recent MI and LVEF or the degree of MR is closely associated with each other and that the use of diuretics is usually the first line of treatment in patients with CHF, a more comprehensive selection of variables in the current study may be attributable to the observed discordance in the results. 24 It is interesting to note was that the patients who developed hemodynamic instability during grafting had significantly lower RVEF, CI and SvO 2 even after the completion of grafting despite similar baseline hemodynamic profiles between the groups in the current trial.…”
Section: Discussionmentioning
confidence: 96%